The views and experiences of Grade 10 Life Sciences teachers on the compulsory practical examination (Perspectives in Education, 2020)
With the introduction of the Life Sciences (LS) Curriculum Assessment Policy Statement (CAPS) in 2012 in South African schools, a practical examination has become compulsory in grades 10 and 11. The LS CAPS policy stipulates the types of practical work that needs to be conducted to develop specific process skills in learners. This interpretive case study explored grade 10 LS teachers’ views on practical work and their experiences of implementing the practical examination. This study was underpinned by two constructs from Rogan and Grayson’s theory of curriculum implementation, namely the profile of implementation pertaining to practical work and the capacity to innovate. Purposive and convenience sampling were used to generate data via questionnaires and individual interviews from grade 10 LS teachers at selected schools of the Umtshezi ward of Estcourt region.